The Effect of Metabolic Syndrome upon the Success of Varicocelectomy. (23rd December 2012) - Ozturk, Ufuk; Sener, Nevzat Can; Nalbant, Ismail; Karabacak, Osman Raif; Ulusoy, Mustafa Gurhan; Imamoglu, M. Abdurrahim
Abstract : We aimed to investigate the impact of metabolic syndrome (MetS) on the varicocele treatment. 101 patients underwent spermatic vein ligation between 2007 and 2010 were retrospectively analyzed. Those patients were divided into two groups as without ( n : 56, Group 1) or with MetS ( n : 48, Group 2). All the patients underwent left microsurgical subinguinal spermatic vein ligation. Groups were compared by the improvement on sperm parameters and spontaneous pregnancy rates at a mean of 19 (±4) months followup. When sperm parameters were compared postoperatively, the significant improvement in total sperm count, motile sperm count percentage, and normal sperm percentage was reported. The groups were compared to each other and the improvement seemed significantly better in Group 1. There was no statistically significant improvement difference in the normal sperm percentage between groups. Spontaneous pregnancy rate after two years was 45% in Group 1 and 34% in Group 2 (P < 0.05 ). Patients with MetS and varicocele improved after surgery, but not as well as the similar group without MetS. This may help to show that MetS can be a factor for male infertility.